INNOVATIVE EDUCATIONAL TECHNOLOGIES IN MATHEMATICS LESSONS (ON THE EXAMPLE OF SINGAPORE EDUCATION) - Gafforova Sarvinoz (Innovate Conferences, 2025)
This article explores the development of methodological competence among trainees in the process of professional development courses. It highlights the significance of enhancing teachers’ skills through innovative teaching methods, modern pedagogical technologies, and reflective practices. The article emphasizes that strengthening methodological competence not only improves the professional growth of teachers but also contributes to the quality and effectiveness of the education system.
Keywords: professional development, methodological competence, pedagogical technology, innovation, reflection, teaching skills.